Leadership and Presenteeism among Scientific Staff: The Role of Accumulation of Work and Time Pressure - Dietz, Carolin; Scheel, Tabea (Frontiers in Psychology, 2017)
The present study examines the joint roles of leadership and stressors for presenteeism of scientific staff. Leaders may have an impact on employees’ health, both directly through interpersonal interactions and by shaping their working conditions. In the field of science, this impact could be special because of the mentoring relationships between the employees (e.g., PhD students) and their supervisors (e.g., professors). Based on the job demands-resources framework (JD-R), we hypothesized that the pressure to be present at the workplace induced by supervisors (supervisorial pressure) is directly related to employees’ presenteeism as well as indirectly via perceptions of time pressure. The conservation of resources theory (COR) states that resource loss resulting from having to deal with job demands weakens the resource pool and therefore the capacity to deal with other job demands. Thus, we hypothesized that accumulation of work moderates the relationship between supervisorial pressure and time pressure, such that the relationship is stronger when accumulation of work is high compared to if accumulation of work is low. Cross-sectional data were obtained from 212 PhD students and postdocs of 30 scientific institutions in Germany. Analysis was performed using the SPSS macro PROCESS (Hayes, 2013). Supervisorial pressure was directly associated with higher presenteeism of employees and indirectly through increased time pressure. Moreover, supervisorial pressure and accumulation of work interacted to predict time pressure, but in an unexpected way. The positive relationship between supervisorial pressure and time pressure is stronger when accumulation is low compared to if accumulation of work is high. It seems possible that job stressors do not accumulate but substitute each other. Threshold models might explain the findings. Moreover, specific patterns of interacting job demands for scientific staff should be considered in absence management.